2021
DOI: 10.1038/s41467-021-24256-9
|View full text |Cite
|
Sign up to set email alerts
|

Revealing thermally-activated nucleation pathways of diffusionless solid-to-solid transition

Abstract: Solid-to-solid transitions usually occur via athermal nucleation pathways on pre-existing defects due to immense strain energy. However, the extent to which athermal nucleation persists under low strain energy comparable to the interface energy, and whether thermally-activated nucleation is still possible are mostly unknown. To address these questions, the microscopic observation of the transformation dynamics is a prerequisite. Using a charged colloidal system that allows the triggering of an fcc-to-bcc trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…It is confirmed that the defects within the crystal texture serve as the primary source of nucleation sites and tend to induce the homogeneous growth of atomic clusters, in terms of quantum‐dot‐level uniform distribution of heterogeneous intermediates. [ 38,40,41 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is confirmed that the defects within the crystal texture serve as the primary source of nucleation sites and tend to induce the homogeneous growth of atomic clusters, in terms of quantum‐dot‐level uniform distribution of heterogeneous intermediates. [ 38,40,41 ]…”
Section: Resultsmentioning
confidence: 99%
“…It is confirmed that the defects within the crystal texture serve as the primary source of nucleation sites and tend to induce the homogeneous growth of atomic clusters, in terms of quantum-dot-level uniform distribution of heterogeneous intermediates. [38,40,41] After that, the following diffraction peaks emerged at 19.1, 33.0, and 34.8° below 0.7 V are indexed to the multi-step alloy reaction products of K 9 Sn 4 (200), K 23 Sn 4 (220), and K 23 Sn 4 (510), respectively. [42] During the charging process, the reverse phase transformation is clearly observed by the disappearance of Na 2 S/Na 2 Se intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…In the last few decades, an enormous library of nanocrystals has been designed using the colloidal approach, which is essentially a phase separation process primarily associated with nucleation and crystal growth stages [116,[153][154][155][156][157][158][159][160][161]207]. In general, it is well known that colloidal systems are distorted solid structures primarily responsible for the nucleation step [208,209]. From this perspective, nucleation as a solute precursor occurs in systems that present their suspended solid phase with a high degree of dispersion, which contributes to the growth stage of nanoparticles [58,[210][211][212][213].…”
Section: Nucleation and Growth Stagesmentioning
confidence: 99%
“…4 Nucleation, the first and most critical step in crystallization, is commonly described by classical nucleation theory (CNT) in the past century, which states that nascent nuclei are directly assembled from atomic or molecular ions in supersaturated environments via a single-step pathway by overcoming a free energy barrier. 5,6 Despite CNT's success in describing a range of crystal nucleation scenarios, 7–10 considerable crystallization phenomena have been suggested to show qualitative and quantitative deviations from CNT; 11,12 e.g. even for single-component nonpolar fluids, there is a few orders of magnitude difference between the CNT predicted and measured nucleation rates.…”
Section: Introductionmentioning
confidence: 99%